Mitogen-Activated Protein Kinase CaDIMK1 Functions as a Positive Regulator of Drought Stress Response and Abscisic Acid Signaling in Capsicum annuum - Kim, Minchae; Jeong, Soongon; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2021)
Protein phosphorylation by kinase is an important mechanism for adapting to drought stress conditions. Here, we isolated the CaDIMK1 (Capsicum annuum drought-induced MAP kinase 1) from dehydrated pepper leaf tissue and functionally characterized it. Subcellular localization analysis revealed that the CaDIMK1 protein was localized in the cytoplasm and nucleus. CaDIMK1-silenced pepper plants exhibited drought-susceptible phenotypes that were characterized by increased transpiration rates, low leaf temperatures, and decreased stomatal closure. In contrast, CaDIMK1-overexpressing (OX) transgenic Arabidopsis plants were hypersensitive to abscisic acid (ABA) from germination to adult growth stages. Furthermore, the CaDIMK1-OX plants were tolerant to drought stress. The transcript levels of several stress-related genes were high in the CaDIMK1-OX plants compared with wild-type plants. Taken together, our data demonstrate that CaDIMK1 acts as a positive modulator of drought tolerance and ABA signal transduction in pepper plants.